Volumetric expanders for low grade heat and waste heat recovery applications. (May 2016) - Imran, Muhammad; Usman, Muhammad; Park, Byung-Sik; Lee, Dong-Hyun
Abstract: Power production from low grade heat and waste heat does not only mitigate environmental impact but also improve energy efficiency and reduce energy cost. The type and design of expander for a low grade heat engine are critical and affect the performance, efficiency and cost of low grade heat and waste heat recovery system. The choice of expansion machine is strongly correlated with operating conditions, working fluid and size of the system. Low grade heat and waste heat recovery systems for electricity production are usually smaller in size. Turbines cannot be used due to their high rotational speed and high cost for waste heat and low grade heat recovery systems less than 50 kWe. Therefore, volumetric expanders are more suitable in low grade heat and waste heat engines for a smaller size. The current paper provides a comprehensive review of volumetric expanders including vane expander, screw expander, scroll expander, and piston expander applications for low grade heat and waste heat recovery using organic Rankine cycle. The operational performance, design optimizations, leakage and frictional losses, modeling techniques for each type of expander has been investigated in detail. Technical constraints and operational performance of expanders have been analyzed followed by the comparative assessment based on their performance, current market status, and economics. The comparative assessment shows that screw expander and scroll expander are most suitable having a relative score of 73.6 and 70.4 respectively on a scale of 100. The vane expanders have the lowest score of 47.2 due to low power range, leakage and frictional losses, and technical complexities.